COMPATIBILITY BETWEEN FOREST SPECIES, SOIL AREA, AND ACCESSIBILITY ON SIDEWALKS - Vendruscolo, Elisiane; Zanon, Magda Lea Bolzan; Bobrowski, Rogério (Floresta, 2023)
The compatibility between the built environment and trees is also a challenge for urban planning. However, there are few guidelines related to the space for tree growth on sidewalks. This research aimed to analyze the space occupied by trees on sidewalks in the city of Frederico Westphalen, RS, Brazil. We used data from 400 trees of 10 species (dendrometric and qualitative variables) and from the urban structure (width of sidewalks and tree bed area) to analyze the relationship between the species according to the soil capacity and pedestrian’s accessibility. It was found that 90.25% of the trees are in places where the sidewalks promote accessibility to pedestrians and that 60.25% of them tree bed areas with adequate capacity, being possible to increase their size to improve the development of the trees in 39.75% of the cases. Regarding the amount of soil required for each tree, it was found that most species (72.25%) would not have an adequate amount of soil, (Situation 1 – sidewalk width x 4). For Situation 2 (tree bed width x 1), 100% of the individuals would not have an adequate amount of soil. We concluded that the method to evaluate the compatibility between soil area and sidewalk accessibility is easy to replicate and helpful for studies on urban trees and urban planning.